Implementing Gender Mainstreaming Policies in Pandeglang Regency Through the Integrated Program for Enhancing Women's Roles Towards Healthy and Prosperous Families - Tania, Reni Reni; Kurnia, Nina; Andayani, Nopi (Program Pascasarjana Universitas Negeri Makassar, 2024)
The Integrated Women's Role Enhancement Program towards Healthy and Prosperous Families (Indonesia: Program Peningkatan Peranan Wanita Menuju Keluarga Sehat Dan Sejahtera / P2WKSS) is a program aimed at enhancing the role of women by employing a coordinated cross-sectoral development approach, focusing on improving family welfare to achieve a better quality of life. This research uses a qualitative descriptive approach to explain various aspects of the implementation of gender mainstreaming policies in Pandeglang Regency. This research focuses on gender mainstreaming policies through integrated programs that enhance women's roles in creating healthy families. In addition, the researcher themselves act as the key instrument in this qualitative research. Researchers use tools such as HP Recorders and mobile cameras. By issuing this regulation, the local government, both executive and legislative, supports the implementation of Gender Responsive Planning and Budgeting (PUG) in Pandeglang Regency. Nevertheless, the General Guidelines for the Implementation of Gender Mainstreaming in Development were established in 2014 through the Regent Regulation of Pandeglang Number 7 of 2014, addressing gender disparities and development in Pandeglang Regency, particularly concerning the implementation of Gender Mainstreaming policies through the Integrated Program for Enhancing the Role of Women Towards Healthy and Prosperous Families (P2WKSS). Through this program, it is hoped that women's empowerment will enhance women's knowledge, skills, and confidence in various aspects of life, especially in education, health, and the economy. The goal of the P2WKSS Program in Pandeglang Regency is to improve family welfare, reduce poverty, and empower women. Through this program, it is expected that women's empowerment will enhance women's knowledge, skills, and confidence in various aspects of life, especially in education, health, and the economy.